THE POWER OF ISLAMIC RESILIENCE AND SELF-IDENTITY OF MUSLIM WOMEN IN PREACHING - Rahmawati, Dewi; Suud, Fitriah M.; M. Suud, Fitriah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
For a Muslim teenage girl, staying true to her identity becomes more challenging as she faces various temptations. This study aimed to explore the role of Islamic resilience and self-identity in Muslim women's da'wah experiences, focusing on the challenges and strength required to maintain their faith and identity in this context. This research was a qualitative study with a phenomenological approach, utilizing in-depth interview to gather detailed insights into the participants' experiences and perspectives on resilience and self-identity in their da'wah activities. The informants of this study were teenagers in their late adolescence, specifically in the age range of 18-21 years. This study examined the experiences and perspectives of Muslim youth in building their identity and how they develop resilience within themselves. This study proved that self-identity of Muslim women had impacted their resilience in da'wah. This study also found out that the dimensions of Islamic resilience can be used by Muslim preachers to be able to survive in maintaining their commitment and identity in preaching